Climate change favors expansion of three Eucalyptus species in China - Mao, Xinjie; Zheng, Huisen; Luo, Guihua; Liao, Songkai; Wang, Ronghao; Tang, Ming; Chen, Hui (Frontiers in Plant Science, 2024)
Eucalyptus has become one of the most widely planted species in tropical and subtropical regions in China, with important economic, ecological, and social values. However, it is currently unclear how climate change will affect different Eucalyptus species. Therefore, it is urgent to investigate the potential distribution and dynamics of Eucalyptus under current and future climate scenarios. In this study, we analyzed the potential distribution patterns of the three main Eucalyptus species (Eucalyptus grandis, Eucalyptus urophylla, and Eucalyptus tereticornis) under current and future climatic conditions (2041-2060 and 2061-2080) using the optimized MaxEnt model, which integrates a variety of environmental data including climate, topography, soil, and human influence. We also identified the main factors affecting the potential distributions of the three main Eucalyptus species. The model indicated that E. grandis exhibited heightened sensitivity to the mean temperature of the coldest quarter (7.0-20.0℃) and annual mean temperature (11.9-24.2℃), whereas E. urophylla displayed heightened sensitivity to precipitation of the warmest quarter (272-1694 mm) and annual precipitation (812-2624 mm). Conversely, E. tereticornis demonstrated heightened sensitivity to annual mean temperature (12.7-24.5℃) and temperature seasonality (63.8-598.9). Under the current climate, E. tereticornis had the widest suitable distribution area (124.91 × 10 4 km²), followed by E. grandis (124.89 × 10 4 km²) and E. urophylla (119.81 × 10 4 km²). Under future climate change scenarios, the suitable ranges of E. grandis, E. urophylla and E. tereticornis will continue to expand.This study highlights the importance of climate change in Eucalyptus distribution and provides quantified potential distribution maps for three Eucalyptus species under current and future climate conditions in China. This research offers valuable scientific insights pertinent to the management and rational site selection for Eucalyptus plantations.